Smart Governance Sebagai Katalisator Green Port: Evaluasi Kesiapan Institusional Pelabuhan Tanjung Emas Semarang dalam Transformasi Maritim Berkelanjutan - Karmanis karmanis; Karjono Karjono; Evyana Diah Kusumawati (Politeknik bumi Akpelni, 2026)
The strategic vision of Tanjung Emas Port Semarang to become a world to transform into a world-class green port confronts critical climate challenges, including tidal flooding that disrupts operations, shipping channel siltation that escalates logistics costs, and container yard congestion that exacerbates carbon emissions. This study aims to assess the port’s institutional readiness in implementing sustainable maritime transformation through the lens of smart governance. A descriptive qualitative approach was employed, with data collection encompassing field observation of service systems and digital infrastructure, regulatory documentation from Pelindo and the Ministry of Transportation, and operational data analysis including water levels and berthing schedules. Thematic analysis focused on three dimensions: digital readiness against physical challenges, integration of environmental sensor data into decision-making systems, and the effectiveness of cross-sectoral coordination between Pelindo and KSOP. The findings reveal that Tanjung Emas Port is in an uneven transitional phase technological infrastructure has been developed, yet data integration for proactive mitigation remains fragmented. Institutional coordination barriers, stemming from data silos and diverging inter-authority priorities, constitute the primary bottleneck hindering collaborative governance. These findings assert that without institutional transformation enabling data sharing and evidence-based decision-making, green technology investments in ports will fail to achieve their optimal impact. Recommendations include establishing an integrated command center and regulatory incentives for collaborative climate action.